Effects of pH changes on phytoplankton biomass - Mohamed, Khairul Nizam (Akademi Sains Malaysia, 2024)
A phytoplankton was incubated for a week to determine the effects of pH changes on its biomass growth in nutrient enrichment incubation samples. In this experiment, a general increase in phytoplankton biomass was observed after 24 hours of incubation, with a similar growth pattern in all incubation samples. By comparing with the same pH range (7.0 to 8.0), Pulau Pangkor (PP) incubation samples achieved the peaks earlier compared to Pulau Redang (PR) samples, although they had a higher increment in biomass. Meanwhile, in extreme pH (4.0 and 9.0) incubation samples, the phytoplankton biomass was observed to thrive well. This present study suggests that the phytoplankton community in Pulau Redang and Pulau Pangkor waters is able to survive in a wide range of pH levels, and the change in ocean pH has no vital impacts on the phytoplankton based on the short-term experiment. © (2024), (Akademi Sains Malaysia). All Rights Reserved.